Methodical bases of functioning of the system model information and telemetric ensuring starts of rockets of space appointment - A.V. Kuimov; A.V. Kononenko (Физика волновых процессов и радиотехнические системы, 2018)
Defines the basic structural-elements of functioning of a system of information telemetry ensuring starts rockets of space appointment. The contents of information processes in the system of information telemetry ensuring starts rockets of space appointment. Highlighted factors in the model functioning sieve. Formed functional dependence parameters characterizing the degree of attainment of the objectives of the system parameters, inputs and system state settings.